Therapeutic options for chronic myeloid leukemia following the failure of second-generation tyrosine kinase inhibitor therapy - George, Binsah; Chan, Kok Hoe; Rios, Adan (Frontiers in Oncology, 2024)
The management of chronic myeloid leukemia in the chronic phase (CML-CP) has witnessed significant advancements since the identification of a common chromosomal translocation anomaly involving chromosomes 9 and 22, which results in the formation of the Philadelphia chromosome driven by the BCR-ABL1 fusion protein. This discovery paved the way for the development of tyrosine kinase inhibitors (TKIs) that target the adenosine triphosphate (ATP) binding site of ABL1 through the BCR-ABL-1 fusion protein. Following the approval of Imatinib by the Food and Drug Administration (FDA) as the first TKI for CML treatment in 2001, the median overall survival (OS) for chronic phase CML (CML-CP) has significantly improved, approaching that of the general population. However, achieving this milestone crucially depends on reaching certain treatment response milestones. Since the introduction of imatinib, five additional TKIs have been approved for CML-CP treatment. Despite the availability of these treatments, many patients may experience treatment failure and require multiple lines of therapy due to factors such as the emergence of resistance, such as mutations in the ATP binding site of ABL, or intolerance to therapy. This review will primarily focus on exploring treatment options for patients who fail second-generation TKI therapy due to true resistance.